Enhancing Student Learning Outcomes through the Communicative Language Teaching Approach - Muhammad Aswad; Andi Mega Januarti Putri; Putu Wahyu Sudewi (STAI Hubbulwathan Duri, 2024)
Traditional teaching methods focused on imparting information often fail to optimize students' communicative abilities in second language acquisition, particularly English. This study explores the effectiveness of Communicative Language Teaching (CLT) in enhancing language skills, including speaking, listening, reading, and writing. A qualitative descriptive approach was employed, utilizing observations and interviews with teachers and students in an English as a Second Language (ESL) learning context in Indonesia. Data collection focused on classroom dynamics, student-teacher interactions, and participants' experiences with CLT. The findings indicate that CLT positively impacts students’ language acquisition. Structured and supportive communication activities fostered significant improvements across all language domains. Students exposed to interactive and authentic communication exercises demonstrated enhanced confidence and proficiency in English. These results underscore the importance of integrating communication-focused methodologies in ESL education. The participatory nature of CLT encourages active engagement, enabling learners to apply language skills in real-life scenarios. Teachers reported that CLT activities also motivated students, promoting collaboration and practical use of language. This study highlights the efficacy of CLT in improving language skills and advocates for its broader adoption in teaching English as a second language in Indonesia. It suggests a shift from traditional, information-based methods to more dynamic, communication-centered approaches, emphasizing the value of student interaction in achieving language proficiency.